Effect of Some Plant Growth Regulators on Growth and Yield Component of Wheat – Plants CV. Bakrajo - Sakri, Faisal Abdulkadir; Ghafor, Noori Hassan; Aziz, Hoshiar Abdula (Sulaimani Journal for Pure and Applied Sciences, 2002)
An investigation was conducted to study the effects of IAA, GA and cytokinine on the growth, yield components and % of protein content of wheat plants Triticum durum cv. Bakrajo Results indicate that the growth regulators caused in significant increase in plant height, number of tillers/ plant, number of kernals/spike and 1000 grain weight. Significant differences were found among the concentration of growth regulators through height, number of leaves/ plant, number of spike / plant, the lenght of spike and number of kernels / spike. also the time of application has significant affected on the length of spike and protein content percentage. As well as the interaction betwwen growth regulators, concentration and time of application showed significant differences.
Keywords: plant grwth regulators Auxin; Gibberellin and Cytokinine; Triticum durum Seedling